Increased rigidity of the chiral centre of tocainide favours stereoselectivity and use-dependent block of skeletal muscle Na(+) channels enhancing the antimyotonic activity in vivo - Talon, Sophie (2001)
1. Searching for the structural requirements improving the potency and the stereoselectivity of Na(+) channel blockers as antimyotonic agents, new derivatives of tocainide, in which the chiral carbon atom is constrained in a rigid α-proline or pyrrolo-imidazolic cycle, were synthesized as pure enantiomers. 2. Their ability to block Na(+) currents, elicited from −100 to −20 mV at 0.3 Hz (tonic block) and 2 – 10 Hz (use-dependent block) frequencies, was investigated in vitro on single fibres of frog semitendinosus muscle using the vaseline-gap voltage-clamp method. 3. The α-proline derivative, To5, was 5 and 21 fold more potent than tocainide in producing tonic and 10 Hz-use-dependent block, respectively. Compared to To5, the presence of one methyl group on the aminic (To6) or amidic (To7) nitrogen atom decreased use-dependence by 2- and 6-times, respectively. When methylene moieties were present on both nitrogen atoms (To8), both tonic and use-dependent block were reduced. 4. Contrarily to tocainide, all proline derivatives were stereoselective in relation to an increased rigidity. A further increase in the molecular rigidity as in pyrrolo-imidazolic derivatives markedly decreased the drug potency with respect to tocainide. 5. Antimyotonic activity, evaluated as the shortening of the time of righting reflexes of myotonic adr/adr mice upon acute drug in vivo administration was 3 fold more effective for R-To5 than for R-Tocainide. 6. Thus, constraining the chiral centre of tocainide in α-proline cycle leads to more potent and stereoselective use-dependent Na(+) channel blockers with improved therapeutic potential.